ENGLISH TEXTBOOK: A CULTURE-BASED ANALYSIS - Trifonia Fahik (Universitas Pendidikan Ganesha, 2020)
This article will present the results of the analysis of the cultural content of a textbook curriculum 2013 entitled When English Rings the Bells used by students in grade VII of junior high school. The data of the research were collected from reading all sections in the book. The cultural content of the book is grouped according to Byram’s theory which classifies the cultural content of the textbook into eleven parts and to analyze the contents of culture in the textbook the theory of Kripenndorf is used as guidance. The analysis showed that ten cultural categories were found in the textbook. The most reviewed cultural content is Social Identity and Social Group, Behavior and Belief and Geography. Cultural content that is displayed is largely Indonesian culture. Target culture is presented in a small portion. Unfortunately, the authors did not present national history and international culture is in this textbook.